The effects of digital transformation on the performance of tax administration: Literature review - AKHANNICH , Otmane; BENAMAR , Fatiha (Revue Internationale des Sciences de Gestion, 2023)
The introduction of digital transformation in order to carry out administrative procedures constitutes a crucial step in ensuring the efforts made to modernize and optimize public administration in general and tax services in particular. Today, we live in a context where technology is considered essential in our daily lives, for this reason, public authorities are required to take advantage of the opportunities provided by digitalization. Moreover, according to the literature review, the impact of digital transformation on public administration is considerable, because it generates structural changes, both in the way in which services are offered to citizens and in the way in which procedures administrative tasks are completed. With this in mind, the main objective sought in this article is to detect the effects that the introduction of the digitalization of administrative procedures has on the effectiveness and efficiency of tax services, in order to achieve the desired performance. Therefore, according to the literature, it has been noted that digital transformation significantly influences the administrative procedures of tax services, by making it possible on the one hand to improve the fluidity of internal processes, to increase the reliability of the data collected, and on the other hand, to increase the efficiency of tax collection and optimize the tax audit process.